Present‐Day Activity of the Anninghe Fault and Zemuhe Fault, Southeastern Tibetan Plateau, Derived From Soil Gas CO2 Emissions and Locking Degree - Yang, Yao; Li, Ying; Li, Youguo; Ji, Lingyun; Gong, Yue; Du, Fang; Zhang, Lei; Chen, Zhi (Earth and space science (Hoboken, N.J.), 2021)
The Anninghe fault (ANHF) and the Zemuhe fault (ZMHF), located in the southeast of the Tibetan Plateau, have a high level of seismic hazard and are among the most active faults in China. This study performed the first measurements of soil gas CO2 at three sites across the ANHF and the ZMHF. The fault locking (FL) depth and extent of different segments of the ANHF and the ZMHF were inverted using the negative dislocation model based on global positioning system velocity data acquired during 2009–2015. Results showed that the degassing intensity of CO2 in the ZMHF is substantially higher than in the ANHF, which is spatially consistent with the degree of inverted FL. The inversion results revealed that the level of coupling, including the locking depth and extent, along the southern segment of the ANHF is markedly greater than in the northern segment of the ZMHF. Soil gas CO2 geochemistry yielded different spatially anomalous features, indicating that the faults have different properties and permeability. The intensive locking of the ANHF and ZMHF segments has reduced permeability through self‐sealing processes, which has restricted the escape of gas from the deep crust. Correspondingly, a creeping fault with a low level of coupling could maintain high permeability, which would be favorable for CO2 migration. Plain Language Summary Soil gas refers to the multicomponent gas enriched in surface soil, which usually shows higher concentrations near faults because of the enhanced permeability. The spatiotemporal distribution of soil gas CO2 on an active fault is sensitive to changes of crustal stress/strain related to seismic activity. Geodynamics can be studied in a variety of ways, such as GPS (global positioning system) and soil gas. In order to figure out the relationship between soil gas CO2 degassing and active fault motion that can be inverted by GPS, we performed the first measurements of soil gas CO2 at three sites across the active faults in southeastern Tibetan Plateau and inverted the spatial fault locking (i.e., a parameter that can reflect the fault motion state) along the faults. We find that the degassing intensity of CO2 is spatially consistent with the degree of inverted fault locking. The high locking degree of the fault constrains the migration of CO2, whereas the creeping fault with a low locking degree is more favorable for the discharge of gas from deeper layers up toward the surface. Key Points Concentrations of soil gas CO2 from the active fault zones were determined Locking degree of different segments of the active faults was inverted CO2 concentrations are correlated with the locking degree of the active faults